HR-LCMS Metabolite Profiling and in silico Evaluation of the Antidiabetic Activity of Methanolic Leaf Extract of Chrozophora rottleri (Geiseler) A. Juss. Ex Spreng. - Nallapaty, Srilakshmi; Malothu, Narender; Konidala, Sathish Kumar; Areti, Anka Rao; Guntupalli, Chakravarthi (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Chrozophora rottleri (Geiseler) A. Juss. ex Spreng. is a well-known traditional medicinal plant with a complex biological profile, though inadequate research has been established on its possible anti-diabetic effects and active metabolite profiling. In the present work, Methanolic leaf extracts (MECR) was used to identify plant metabolites by HR-LCMS analysis, and in silico docking studies and screened to assess their hypoglycaemic potential. Materials and Methods: In the preliminary investigation, the druggable abilities of the compounds were examined using the Swiss ADME in silico tool. The phytochemicals were virtually evaluated to determine their binding efficacies against the following proteins: sodium-glucose co-transporter 1 (PDB ID: 5EQG), insulin receptor (PDB ID: 1IR3), glucose co-tra ns porter 1 (PDB ID: 3DH4), and human dipeptidyl peptidase-IV (DPP-IV) (PDB ID: 4A5S). Besides, the impact of MECR on oxidative stress was evaluated by DPPH, H2O2, and FRAP assays. Results: In the HR-LCMS analysis, a total of 31 phytochemicals were found, including 14 flavonoids, 7 glycosides, 3 phenols, and a few carbohydrates, fatty acids, and alkaloids. Most phytochemicals showed favourable oral bioavailability and druggable characteristics, with 0 or 1 violation of Lipinski’s criteria. In contrast to dapagliflozin, a flavonoid compounds remikiren (AA12) and aureusidin (AA11); and an isoflavone genistein 8-C-glucoside (AA6) demonstrated greater affinity for 5EQG in docking study. A phenolic compound, cryptochlorogenic acid (AA1), had a notably higher binding affinity for 4A5S in comparison to vildagliptin. Conclusion: The present work has undertaken the first-ever investigation of bioactive phytochemicals and in silico hypoglycaemic profiling of leaves of C. rottleri. It can provide insight into further research for the discovery of new potential anti-diabetic agents.
Keywords: C. rottleri; Antidiabetic activity; Antioxidant activity; Docking; HR-LCMS; in silico study